Illegal Mining and Sustainability Performance: Evidence from Ashanti Region, Ghana - Nti, Thomas; Chen, YinFei; Quayson, Bright Parker; Agyei, Fred Yeboah (International Journal of Scientific Research and Management (IJSRM), 2020)
As illegal mining in Ghana has become increasingly rampant ever, this study aimed at examining the effect of illegal mining on the dimensions of sustainability performance among crop farmers and the challenges they face because of illegal mining in the Ashanti Region, Ghana.To investigate the intriguing connections among illegal mining and sustainability performance among crop farmers, this paper draws on multidisciplinary literature and collects empirical data from 250 respondents in the Atwima Nwabiagya and Atwima Mponua Districts, Ghana to test the proposed model and hypotheses using structural equation modeling.All the three (3) elements or paradigms of sustainability performance were negatively affected by illegal mining activities. It was also observed that a significant positive relationship exists among all the elements of sustainability performance hence a consequence on one element may affect the other.Unlike most research on illegal mining that has been theoretical, this study represents one of the few empirical analyses of how illegal mining may affect sustainability performance